The Needs of Beginning Thai BIPA Learners on Indonesian Cultural Content - Ari Ambarwati; Prayitno Tri Laksono; Sri Wahyuni; Ifit Novita Sari (CV. Media Digital Publikasi Indonesia, 2023)
Indonesia and Thailand share the same cultural knowledge regarding rice food consumption and the heroic epic Panji or Inao. However, research exploring learning materials about this two cultural knowledge as BIPA learning materials for beginner Thai BIPA learners has not been intensively conducted. This research focuses on efforts to identify the need for Indonesian-Thai cultural content material for BIPA students at the beginner level. This research design uses ADDIE by adapting the first two steps, namely first, compiling questionnaires and interviews with BIPA Thai elementary students and teachers to obtain projections of the needs and preferences of non-text BIPA textbooks containing Inao's story. Second, conduct a needs and preferences analysis of the results of questionnaires and interviews of beginner-level BIPA Thai learners. The respondents of this study were six BIPA students from the State University of Malang, Walalailak University of Thailand, and the Islamic University of Malang. The results showed that the culture of rice consumption, the story of Inao or Panji, and Indonesian tourist attractions that became world heritage designated by UNESCO are interesting and need to be the content of BIPA learning materials, with the medium of electronic books, BIPA pages, and social media platforms (IG, FB, Twitter, and Youtube). The implication of this research is the preparation of BIPA learning designs for Thai BIPA students with cultural content of rice consumption, the story of Panji or Inao, and Indonesian tourist attractions that are UNESCO world heritage